PENINGKATAN KINERJA GURU DALAM MENYUSUN SILABUS DAN RPP MENGGUNAKAN MICROSOFT WORD MELALUI SUPERVISI AKADEMIK PENGAWAS DI MI BINAAN PRINGAPUS KABUPATEN SEMARANG - ADI HERMAWAN (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2021)
Education must be able to form a complete human being who is described as a human being who has personal characteristics who understand psychosocial dynamics and their cultural environment. The educational process must include: (a) the development of faith, piety, (b) the development of national, state, democratic, and personality insights, (c) mastery of science and technology, (d) development, appreciation, appreciation, and artistic expression, and (e) the formation of physically and mentally healthy human beings. The process of human formation above is essentially a process of cultivating and empowering students that lasts a lifetime. The educational process carried out above is unlikely to be achieved if teacher performance is still low, especially in making school planning. The purpose of this supervisory action research (PTKp) is to find out the extent to which teacher performance improvement in compiling the syllabus and lesson plans using Microsoft Word in MI assisted by the Ministry of Religion, Kec. Pringapus Kab. Semarang Academic Year 2018/2019. In this supervisory action research (PTKp) it was carried out in 3 cycles, from the results of the actions taken it was proven to be able to improve teacher performance in compiling syllabus and lesson plans using Microsoft Word. From the average results of 59.09% in the first cycle, it can increase to 70% in the second cycle, and 85.45% in the third cycle. And it has reached the ideal standard, which is at least 85%, and the average reaches 100% completeness. The results of this action research indicate that the supervision of supervisors through academic supervision is effective and can improve teacher performance in compiling the Syllabus and lesson plans using Microsoft Word at the Ministry of Religion's Regional Assisted Elementary Schools, Kec. Pringapus Kab. Semarang Academic Year 2016-2017. ABSTRAKPendidikan harus mampu membentuk manusia seutuhnya yang digambarkan sebagai manusia yang memiliki karakteristik personal yang memahami dinamika psikososial dan lingkungan kulturalnya. Proses pendidikan harus mencakup: (a) penumbuh kembangan keimanan, ketakwaan, (b) pengembangan wawasan kebangsaan, kenegaraan, demokrasi, dan kepribadian, (c) penguasaan ilmu pengetahuan dan teknologi, (d) pengembangan, penghayatan, apresiasi, dan ekspresi seni, serta (e) pembentukan manusia yang sehat jasmani dan rohani. Proses pembentukan manusia di atas pada hakekatnya merupakan proses pembudayaan dan pemberdayaan peserta didik yang berlangsung sepanjang hayat. Proses pendidikan yang dilaksanakan di atas tidak mungkin akan dapat tercapai kalau kinerja guru masih rendah terutama dalam membuat perencanan sekolah. Tujuan dari penelitian tindakan Kepengawasan ( PTKp ) ini adalah untuk mengetahui sejauh mana Peningkatan Kinerja Guru dalam menyusun Silabus dan RPP menggunakan Microsoft Word di MI Binaan Wilayah Kemenag Kec. Pringapus Kab. Semarang Tahun Pelajaran 2018/2019. Dalam penelitian tindakan Kepengawasan ( PTKp ) ini dilakukan dalam 3 siklus, dari hasil tindakan yang dilakukan terbukti dapat meningkatkan kinerja guru dalam menyusun Silabus dan RPP menggunakan Microsoft Word. Dari hasil rata-rata 59,09 % pada siklus I, dapat meningkat menjadi 70 % pada siklus II, dan siklus ke III 85,45 %.dan telah mencapai standar ideal, yaitu minimal 85%, dan rata rata mencapai 100 % ketuntasan. Hasil penelitian tindakan ini menunjukkan bahwa pembinaan pengawas melalui supervisi akademik efektif dan dapat meningkatan kinerja guru dalam menyusun Silabus dan RPP menggunakan Microsoft Word di SD Binaan Wilayah Kemenag Kec. Pringapus Kab. Semarang Tahun Pelajaran 2018-2019.